2011
DOI: 10.1016/j.jmb.2011.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Characterization of Lysophosphatidic Acid Binding by a Humanized Monoclonal Antibody

Abstract: Lysophosphatidic acid (LPA) is a common product of glycerophospholipid metabolism and an important mediator of signal transduction. Aberrantly high LPA concentrations accompany multiple disease states. One potential approach for treatment of these diseases, therefore, is the therapeutic application of antibodies that recognize and bind LPA as their antigen. We have determined the x-ray crystal structure of an anti-LPA antibody (LT3015) Fab fragment in its antigen-free form to 2.15 Å resolution and in complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…1A). Based on the LT3015 fragment antigen-binding LPA(14:0) and fragment antigen-binding LPA(18:2) crystal structures, the LPA epitope consists of the glycerolphosphate group plus the juxtaposed C1-C8 carbon atoms of the acyl chain (29). As visualized in both cocrystal structures, this portion of the bound LPA hydrocarbon chain is fully extended and forms extensive intermolecular hydrophobic contacts with the antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Based on the LT3015 fragment antigen-binding LPA(14:0) and fragment antigen-binding LPA(18:2) crystal structures, the LPA epitope consists of the glycerolphosphate group plus the juxtaposed C1-C8 carbon atoms of the acyl chain (29). As visualized in both cocrystal structures, this portion of the bound LPA hydrocarbon chain is fully extended and forms extensive intermolecular hydrophobic contacts with the antibody.…”
Section: Discussionmentioning
confidence: 99%
“…1B). The production and characterization of the two humanized IgG1k mAbs, LT1009 and LT3015, 3 which specifically recognize S1P and LPA, respectively, and the structural basis for lipid recognition are described elsewhere (28,29). These antibodies directly compete with carrier proteins for binding target lipids in vitro; the equilibrium binding curve for LT3015 binding LPA shifts toward weaker apparent affinity as the concentration of fatty acid-free (FAF)-BSA is increased (Fig.…”
mentioning
confidence: 99%
“…113115 Similarly, conventional antibodies tend to accommodate short linear peptides and nucleic acid polymers within grooves formed from both heavy- and light-chain CDRs. 104 Four studies have reported structures of camelid V H Hs in complex with haptens and peptides (Table 2); the recognition mechanism of all but one (a methotrexate-specific V H H with a non-canonical binding site involving framework region (FR)3 residues located below CDR1 113 ) was basically similar to that of conventional antibodies, with the hapten-binding pocket formed from two or more CDRs and extending in some instances into the former V L interface.…”
Section: Single-domain Antibodies Directed Against Small Moleculesmentioning
confidence: 99%
“…Conversely, activating Gα s coupled receptors by adrenaline, glucagon and dihydrexidine turns on the cAMP-dependent protein kinase A (PKA) signaling pathway and promotes LAST1/2 activity, resulted in YAP suppression (24,25). Therapeutic approaches targeting GPCR to attenuate YAP/Hippo pathway in cancers have been evaluated in clinic trials, including S1P-blocking antibody Sphingomab and Phosphatase-resistant LPA analog (26,27). In pre-clinical studies, G protein-coupled β-adrenergic receptor agonist dobutamine has been proposed as anti-cancer treatments (28).…”
Section: Gα 12/13 Gα Q11 Gα S and Gpcr Signalingmentioning
confidence: 99%